Psychology 300, Online Degree Completion Program Assessment
In order to better understand how those outcomes came to be, our Teaching & Learning Innovations & Extended University leadership group conducted a retrospective analysis of the process. We reflected on the entire process of moving the program from an off site, in person program (Goleta) to fully online. In all, this process took place over about 2 years. Addressing the challenges in a single high DWF class does not happen in isolation, with a single faculty member, or with a single intervention. This understanding comes from both our successes with this program and past experiences, and it is reinforced by scholarship in our field.